Diets of freely grazing and captive reindeer during summer and winter - Nieminen, Mauri; Heiskari, Ulla (Rangifer, 1989)
The chemical composition and nutritive value of different forage plants and commercial feeds of reindeer were studied by standard methods in the Finnish reindeer herding area during 1980-86. The nutritive values, particularly the protein and mineral contents, of ground lichens (Cladina spp.) and arboreal lichens (Alectoria spp.) were very low compared to forest wiregrass (Deschampsia flexuosa), summer forage plants and commercial feeds. The crude protein and mineral content of reindeer summer food was very high. The energy content of lichens and commercial feeds was high and they are an important source of energy for reindeer in winter. Vapaasti laiduntavien ja tarhaporojen ravinto kesa 11a ja talvella. Abstract in Finnish / Yhteenveto: Poron ravintokasvien ja kaupallisten rehujen kemiallista koostumusta ja ravintoarvoja tutkittiin vakiomenetelmin Suomen poronhoitoalueella vuosina 1980-86. Poronjakalien {Cladina spp.) ja luppojen {Alectoria spp.) ravintoarvot ja valkuais- ja kivennaisainepitoisuudet olivat hyvin alhaiset verrattuna metsalauhaan {Deschampsia flexuosa), kesaravintokasveihin ja kaupallisiin rehuihin. Poronjakalien ja kaupallisten rehujen energiapitoisuus oli kuitenkin korkea ja niista poro saa nopeasti tarvitsemaansa energiaa talvella. Fritt betande och inhagnade renars matsedel under sommar och vinter i Finland. Abstract in Swedish / Sammandrag: Man har undersokt den kemiska sammansattningen och naringsvardet av olika foderplanter och kommerciella fodermedel under åren 1980-86. Naringsvardet, sarskilt innhållet av protein i renlavar {Cladina spp.) och tradlavar (Alectoria spp.) var mycket lågt sammanliknat med smyla (Deschampsia flexuosa), sommarbetesplanter och kommerciella fodermedel. Råprotein och mineralinnehåll i renenes som-marbetes-foder var mycket hogt. Energiinnehållet av lavar och kommerciella fodermedel var ho gt och dessa år viktiga energikallor for renen i vintern.